Dampak Deklarasi Capres-Cawapres terhadap Dinamika Pasar Modal di Indonesia: - Dedi Junaedi; Rio Kartika Supriyatna; Muhammad Rizal Arsyad,; Faisal Salistia; Sholikul Hadi; Abdul Husenudin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This research aims to analyze the impact of the declaration of the presidential and vice presidential candidates on the dynamics of the capital market in Indonesia. The method used is quantitative analysis with a multiple dummy variable regression approach. The results prove that the declaration of the presidential and vice presidential candidates has a significant impact on the dynamics of the capital market in Indonesia. The movements of conventional stock indices (Composite and LQ45) and sharia stock indices (JII70 and ISSI) are significantly influenced by the declaration of the presidential and vice presidential candidate pairs for the 2024 Election, with quite strong correlations (Composite 0.6242, LQ45 0.6805, JII70 0.7968, and ISSI 0.5181). The declaration of the Anies-Muhaimin pair (Capres1) is positively correlated with the movement of the Composite stock index, LQ45, JII70 and ISSI. Meanwhile, the declaration of the Ganjar-Mahfudz pair (Capres 2) and the Prabowo-Gibran pair had a negative correlation with the movement of the Composite stock index. Research facts show that the capital market responded positively to the declaration of pair number 1 (Anies-Muhainin). On the other hand, the capital market responded negatively to the declarations of pair Number 2 (Prabowo-Gibran) and pair Number 3 (Ganjar-Mahfudz). The capital market was under greater pressure after the Prabowo-Gibran pair was declared. Market pressure is greater on Prabowo-Gibran compared to the Ganjar-Mahfudz pair and the Anies-Amin pair. Keywords: presidential and vice presidential candidate declaration, conventional capital market, sharia capital market